Duties And Functions Within Parliament To Improve The Welfare Of The People As Autonomy Realization In District Of Blora - Yusuf Abdurrohman (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
The problem of this research is duties and functions of Parliament in improving the welfare of the people as the embodiment of Autonomy, implementation duties and functions of Parliament in improving the welfare of the people as the embodiment of the Autonomy Region in Blora and constraints and solutions in implementing duties and functions of Parliament in improving the welfare of the people as the embodiment of the Autonomy Region in Blora. The approach used in this study is a sociological juridical approach. Type in this research is descriptive analysis, research that seeks to describe and analyze a phenomenon, events, events that occurred while now.Based on the results of this study are legislative Council Blora Regency is an institution intended to carry out environmental management throughout Blora through attribution has been set in legislation. In the execution of its duties and functions, the People's Council of Blora Regency is in conformity with the rules, but still impressed normative. This is caused by the authority granted unlike in the New Order era. Parliament is currently executing government area parallel to the head area. In practice the more dominant regional head for government affairs and regional autonomy. In the execution of duties, powers, and functions of DPRD Blora there are several constraints such initiatives are largely derived from the executive regulations, a lack of understanding of the problems of the region, the lack of clear criteria for oversight of the executive. The solution is DPRD Blora must improve human resources-related issues of legal drafting, budget, and control of the area, especially the chosen area (electoral district) council members concerned.Keywords: Duties and Functions; Parliament; Local Autonomy.